Real-world outcomes following switching from anti-TNF reference products to biosimilars for the treatment of psoriasis - Rachel C. Ruda; Katherine A. Kelly; Steven R. Feldman (Taylor & Francis Group, 2023)
Tumor necrosis factor (TNF) inhibitors improved clinical outcomes for patients with psoriasis but are limited by their high cost. There are several biosimilar options approved for the treatment of psoriasis which provides a lower-cost alternative and the potential to increase treatment availability for both biologically naïve and bioexperienced patients. Numerous phase III randomized controlled trials (RCTs) have investigated the effects of switching from biologics to biosimilars; biosimilars had comparable safety and efficacy to their reference products. Real-world evidence may provide complementary information on the expected performance of biosimilars. In this literature review, we analyzed data from real-world studies on switching from biologics for psoriasis to their biosimilars. Effectiveness and safety profiles were comparable when switching from biologics to biosimilars of adalimumab, etanercept, and infliximab. These studies are limited by their sample sizes, duration of follow-up, and single-arm designs without control groups. Based on available real-world evidence, patients may safely and effectively undergo switching to biosimilar therapies for the treatment of psoriasis.